Segner-Hasund Harmony Box in Clinical Practice - A. Řeháček; M. Janega; P. Michalík; P. Hofmanová; T. Dostálová (Czech Dental Chamber, 2011)
Cephalometric x-ray image analysis is excellent tool for diagnosis a treatment planning in orthodontics, prosthodontics and maxillofacial surgery. Segner-Hasund harmony box describes facial skeleton in complex and evaluates single cephalometric measurements from the point of view of measurements correlation. Three case reports demonstrate using Segner-Hasund harmony box in practice.